Thermal nociceptive properties of trigeminal afferent neurons in rats - Nemenov Michael I; Klukinov Mikhail; Manering Neil A; Cuellar Jason M; Yeomans David C (SAGE Publishing, 2010)
Abstract Background Although nociceptive afferents innervating the body have been heavily studied form many years, much less attention has been paid to trigeminal afferent biology. In particular, very little is known concerning trigeminal nociceptor responses to heat, and almost nothing in the rat. This study uses a highly controlled and reproducible diode laser stimulator to investigate the activation of trigeminal afferents to noxious skin heating. Results The results of this experiment demonstrate that trigeminal thermonociceptors are distinct from themonociceptors innervating the limbs. Trigeminal nociceptors have considerably slower action potential conduction velocities and lower temperature thresholds than somatic afferent neurons. On the other hand, nociceptors innervating both tissue areas separate into those that respond to short pulse, high rate skin heating and those that respond to long pulse, low rate skin heating. Conclusions This paper provides the first description in the literature of the in vivo properties of thermonociceptors in rats. These finding of two separate populations aligns with the separation between C and A-delta thermonociceptors innervating the paw, but have significant differences in terms of temperature threshold and average conduction velocities. An understanding of the temperature response properties of afferent neurons innervating the paw skin have been critical in many mechanistic discoveries, some leading to new pain therapies. A clear understanding of trigeminal nociceptors may be similarly useful in the investigation of trigeminal pain mechanisms and potential therapies.